Clinical delineation of GTPBP2‐associated neuro‐ectodermal syndrome: Report of two new families and review of the literature. Issue 5 (19th March 2019) - Carter, Melissa T.; Venkateswaran, Sunita; Shapira‐Zaltsberg, Gali; Davila, Jorge; Humphreys, Peter; ,; Kernohan, Kristin D.; Boycott, Kym M.
Abstract : The GTPBP2 gene encodes a guanosine triphosphate (GTP)‐binding protein of unknown function. Biallelic loss‐of‐function variants in the GTPBP2 gene have been previously reported in association with a neuro‐ectodermal clinical presentation in six individuals from four unrelated families. Here, we provide detailed descriptions of three additional individuals from two unrelated families in the context of the previous literature. Both families carry nonsense variants in GTPBP2 : homozygous p.(Arg470*) and compound heterozygous p.(Arg432*)/p.(Arg131*). Key features of this clinically recognizable condition include prenatal onset microcephaly, tone abnormalities, and movement disorders, epilepsy, dysmorphic features, retinal dysfunction, ectodermal dysplasia, and brain iron accumulation. Our findings suggest that some aspects of the clinical presentation appear to be age‐related; brain iron accumulation may appear only after childhood, and the ectodermal findings and peripheral neuropathy are most prominent in older individuals. In addition, we present prenatal and neonatal findings as well as the first Caucasian and black African families with GTPBP2 biallelic variants. The individuals described herein provide valuable additional phenotypic information about this rare, novel, and progressive neuroectodermal condition. Abstract :